Hosts and Commensal Bacteria Synergistically Antagonize Opportunistic Pathogens at the Single‐Cell Resolution - Sheng Zhang; Ziguang Wang; Anqi Liu; Jinshu Li; Jingjing Zhuang; Xiaowen Ji; Paul I. Mulama; Maoye Li; Haiqun Cao; Eng‐King Tan; Wei Liu (Advanced Science)
Abstract Natural microbes coexist in a diverse species population with competition for space and nutrient resources. However, the molecular mechanisms underpinning the regulatory networks of microbes among themselves and with their host are still in infancy. Here, it is reported that Drosophila and the commensal Lactiplantibacillus plantarum form an alliance to compete with the pathogenic Serratia marcescens using the integrated three‐species model system. In the dual‐species model, larvae diminish the L. plantarum population, but reversibly increase lactate production through altering its transcriptional reprogramming. In the tripartite‐species model, larvae facilitate the growth of L. plantarum that confers colonization resistance against S. marcescens. On the other hand, S. marcescens launches sophisticated arms race strategies to impair colonization resistance by sensing lactate derived from L. plantarum. More importantly, the S. marcescens population challenged with Drosophila and L. plantarum adaptively diverge into virulent and reduced virulence subclusters with an increase in resistance heterogeneity. To form the alliance with Drosophila, heterogeneity in lactate generation is broadened among L. plantarum subpopulations. Altogether, these findings provide an insight into the host‐commensal‐pathogen symbiosis at both bulk and single‐cell resolutions, advancing fundamental concepts of precise manipulation of bacterial communities.